THE EFFECT OF FAMILY LIVING ARRANGEMENT ON DELAYED SEXUAL DEBUT AMONG FEMALE TEENAGERS IN INDONESIA - Anissa Rizkianti; Ika Saptarini; Siti Masitoh (Research Centre for Population, Indonesian Institute of Sciences, 2020)
Delaying sexual debut is essential to prevent female teenagers from early sexual activity that can expose them to the risks of unintended pregnancy, unsafe abortion, and sexually transmitted infections, including HIV. Family structure has a critical role in shaping adolescents’ sexual behaviors. However, this issue remains poorly understood in Indonesia. The study aims to assess the association between family living arrangement and delayed sexual debut among Indonesian female youth. The study analyzed data of unmarried Indonesian adolescents age 19-24 from Indonesia Demographic and Health Survey (DHS) 2017, using descriptive statistics and multivariate logistic regression. After controlling for sex of household head, educational status and knowledge of HIV/AIDS, female teenagers who lived with both parents were more likely to postpone sexual intercourse; however, this effect was not statistically significant. The family living arrangement has important consequences in terms of sexual development among female teenagers. Interventions on strengthening supportive atmosphere within the family and improving parent-adolescent relationships are critical in reducing teenagers' vulnerability to sexual risk-taking behaviors.